Mangrove Density Relationship with Abundance of Bivalva In Sungai Alam Village Bengkalis Sub District Bengkalis Regency Riau Province - Rosalina M Siahaan; Nur El Fajri; Adriman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted from January-February 2014 in Sungai Alam Village,Bengkalis Sub District, Bengkalis Regency, Riau Province. The aim of research is tounderstand the relationship between mangrove density with abundance of bivalva.The result showed that 7 species of mangrove were found: Avicennia alba,Sonneratia alba, Rhizopora apiculata, R. mucronata, R. stylosa, Lumnitzera racemosa,Xylocarpus granatum. Density of mangrove between 2.834-4.233 trees/Ha. In eachstation, there were 2 kinds of bivalva such as Polymesoda expansa and Pharus sp. Theabundance of bivalva between 834 – 2.000 organism/Ha. The highest abundance wasobtained in the 3rd stasion (2000 organism/Ha), while the lowest was obtained in the 1ststation (834 organism/Ha). To found out relation between mangrove density and bivalvaabundance, the data were analized by using simple linier regretion. The regression line testbetween mangrove density with abundance of bivalva showed the equation Y= 272,3 +0,194 X with determine coefisien (R2) is 0,266 or 26,6 %.Keywords : Mangrove density, bivalva abundance, Sungai Alam, Bengkalis, Riau